Effectiveness of Countering Acts of Terrorism Within Asean: Challenges and the Path Forward - Dini Dewi Heniarti; Edi Setiadi (Unissula, 2025)
Acts of terrorism have emerged as a non-traditional security challenge, exacerbating the intricacies of the geopolitical security discourse and the equilibrium of power while remaining a prevalent menace in the Southeast Asia region. This article seeks to explore effective strategies to confront the evolving threat act of terrorism to establish security and promote peace in the area. This study employs socio-legal approach by analyzing legal materials, primarily ASEAN policies and secondary data. Data analysis was conducted qualitatively, and the results were delivered descriptively to answer the research questions. As a regional organization, the approach used by ASEAN to handle acts of terrorism is ineffective because of the Asian Way. This principle prevents ASEAN from overcoming the issue because it focuses on non-binding, non-specific measures without establishing a mechanism to monitor progress against these acts of terror. This research offers novelty by encouraging the reevaluation, reorientation, and reformulation of the ASEAN Way concerning the rapid global dynamics and transnational challenges. It will strengthen the main pillars, adapt to global realities, and require commitment from all member countries.